A two-experiment approach to physical modelling: damage and failure under high-rate loading. (October 2022) - Zhang, Jingwen; Davey, Keith; Darvizeh, Rooholamin; Sadeghi, Hamed
Abstract: The use of scaled experiments and physical models to investigate the complex responses of large-scale structures under high-rate loading is well-established. The approach however is recognised to suffer from deficiencies when substitute materials are involved as sought material-property combinations are not always available in readily accessible materials. This practical issue is one of scale effects where the behaviour of a scaled-physical model can depart sometimes markedly from the full-scale response. This was certainly the situation prior to the recent arrival of a new scaling theory called finite similitude with the establishment of new similitude rules but at the cost of additional scaled experiments at different scales. This paper examines the benefits of two scaled experiments in physical modelling to examine whether the existing problems posed by the paucity of material behaviours can be remedied by combining the results of two experimental trials at different scales. The focus here is on pressure-vessel response when exposed to projectiles and blast loading to provide non-trivial behaviours that are typically not easily captured with a single scaled experiment. The investigation is performed with the aid of a commercial finite element analysis software and the Conwep blast-loading analysis to reveal that the flexibility provided by two scaled models is significant. Although perfect replication of full-scale behaviour is not always achievable the ability to design scaled experiments with combinations of standard materials is shown to provide good levels of accuracy. Highlights: A new two-experiment approach to physical modelling. A procedure for material selection founded on a standard impact test. A demonstration of how two scaled experiments can capture high-rate responses. Failure analysis for pressure vessels made of dissimilar materials and loaded at rate.